ALIH AKSARA DAN ALIH BAHASA TEKS HIKAYAT SI MISKIN - Yovi Ersariadi; Hasanuddin WS Hasanuddin WS; Zulfadhli Zulfadhli (Faculty of Languages and Arts, Universitas Negeri Padang, 2014)
This article was written to (1) describe of teks story about The Story of Si Miskin, (2) describe the translation of story about The Story of Si Miskin, (3) describe change language of story about The Story of Si Miskin. The objeck of this study were story about The Story of Si Miskin. The text was data processing by four step, is roundup of data, describe of the text, translation, and change language. The finding of the study is avalaible of text about The Story of Si Miskin in Latin script and Indonesian language and more words that indicate old language charactheristic.